Metabolomics of sebum reveals lipid dysregulation in Parkinson’s disease - Eleanor Sinclair (Nature Portfolio, 2021)
Studies of metabolites in neurodegeneration have not yet used sebum as a source fluid. Here the authors demonstrate the potential of metabolomics of sebum samples from individuals with Parkinson’s disease and controls.